Representasi Father Involvement Dalam Film Stranger Things Season 2 - Nastiyar, Firdaus Algim; Tanjung, Sumekar (Program Studi Ilmu Komunikasi UII, 2024)
The image of masculinity positioning fathers as central figures in earning a living has implications for the lack of paternal involvement in child-rearing, known as fatherlessness or daddy issues. This research uses the film “Stranger Things” (2017) to provide insights into how father involvement is represented. The study aims to understand how elements of father involvement are depicted in the film “Stranger Things” (2017). The research employs Roland Barthes’ semiotic analysis method, which examines the significance of denotation and connotation. The results show that aspects of father involvement represented in the film are divided into four indicators: (1) authoritarian attitude, (2) portrayal of feminist men, (3) role model for children, and (4) temperamental nature. Thus, it can be concluded that father’s involvement in child-rearing can open new windows into breaking the boundaries of the image of masculinity in societal reality.